2008
DOI: 10.1007/s00220-008-0460-2
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Manifolds for a Smoluchowski Equation on the Unit Sphere

Abstract: The existence of inertial manifolds for a Smoluchowski equationa nonlinear Fokker-Planck equation on the unit sphere which arises in modeling of colloidal suspensions -is investigated. A nonlinear and nonlocal transformation is used to eliminate the gradient from the nonlinear term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Indeed, spectral gap conditions have been widely used in the literature to establish the existence of inertial manifolds for many dissipative evolution equations (cf. [1,13,17,18,19,32,34]). However, for a system that lacks the spectral gap condition, in their pioneering work [26], Mallet-Paret and Sell have introduced the so-called spatial averaging method to prove the existence of inertial manifolds for a three-dimensional reaction-diffusion equation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, spectral gap conditions have been widely used in the literature to establish the existence of inertial manifolds for many dissipative evolution equations (cf. [1,13,17,18,19,32,34]). However, for a system that lacks the spectral gap condition, in their pioneering work [26], Mallet-Paret and Sell have introduced the so-called spatial averaging method to prove the existence of inertial manifolds for a three-dimensional reaction-diffusion equation.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the results concerning equilibria and kinetics for the Maier-Saupe potential can be found in [1] - [4], [6], [7], [10] - [14] and [19]. Recently it was shown that the system has inertial manifolds in both S 1 and S 2 ([17]- [18]).…”
Section: Kineticsmentioning
confidence: 99%
“…Using the Cole-Hopf transform, a large class of diffusive Burgers equations including BSE and QSE will be shown to possess inertial manifolds in both one and two space dimensions. The idea to transform the equation was also developed and used by the author to prove the existence of inertial manifolds for a class of nonlinear Fokker-Planck equations, which appear in the modeling of nematic polymers (see [28,29,30]). Rather than the Cole-Hopf transform, the author developed a nonlinear nonlocal transform which also eliminates the first-order derivatives from the equation, thus allowing the equation to satisfy the spectral-gap condition.…”
Section: Introductionmentioning
confidence: 99%